2002
DOI: 10.1308/003588402760978166
|View full text |Cite
|
Sign up to set email alerts
|

The fourteen-day rule and colorectal cancer

Abstract: Objective: To examine the effect of the fourteen-day rule on the colorectal service of a district general hospital. Methods: Prospective audit of all patients referred by general practitioners to the colorectal service of a district general hospital serving a population of approximately 300,000 people. The main outcome measures were: (i) mean interval in days from referral to first clinic appointment; (ii) first clinic appointment to diagnosis; and (iii) overall interval from referral to diagnosis. Results: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 2 publications
2
28
1
Order By: Relevance
“…This should, in theory, have a negative impact on all other aspects of the service, although no evidence of this has been found to date. Three studies reported a decline in the routine endoscopy waiting lists following the introduction of the TWR [11,25,45], possibly due to an increased awareness of the guidelines for patient referrals, the more efficient organisation of services or the introduction of nurse endoscopists to cope with increased demand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This should, in theory, have a negative impact on all other aspects of the service, although no evidence of this has been found to date. Three studies reported a decline in the routine endoscopy waiting lists following the introduction of the TWR [11,25,45], possibly due to an increased awareness of the guidelines for patient referrals, the more efficient organisation of services or the introduction of nurse endoscopists to cope with increased demand.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the TWR on long term survival remains unknown [11]. Many studies have reported no significant difference in the stage of the disease in CRC patients referred via the TWR compared with other referral routes [12,14,19,26,31].…”
Section: Discussionmentioning
confidence: 99%
“…There are widespread examples of QI schemes and service redesign to achieve this result. 44,[47][48][49][50][51][52][53] However, the rigid nature of the measures that underpinned star ratings has been criticized for encouraging 'management to measure' , 44,50,54 although it is questionable how great the effect of this was. 46 In addition, gaming 44 48,51,55 and unsophisticated falsification of data 44,46,48 were also noted.…”
Section: Implicit Incentives -Damage To Reputation Kudos and Censurementioning
confidence: 99%
“…Thus, reducing wait times may in turn confer psychosocial benefits. Moreover, a wait period of 8 weeks to reach a diagnosis in a high-risk patient population appears particularly unjustifiable when recently published series reported good compliance to a '2-week wait rule' from referral to treatment among breast and colorectal cancer patients [26,27].…”
Section: Discussionmentioning
confidence: 99%